2008
DOI: 10.1021/jf7036664
|View full text |Cite
|
Sign up to set email alerts
|

Tastes and Structures of Bitter Peptide, Asparagine-Alanine-Leucine-Proline-Glutamate, and Its Synthetic Analogues

Abstract: Asn-Ala-Leu-Pro-Glu (NALPE) is a strong bitter peptide with a minimum response threshold (MRT) of 0.074 mM. To elucidate the relationship of spatial structure and bitterness on peptides, NALPE and its analogues, NALPW, NALPS, NALPL, NALPP, NALPD, and NALPR, were synthesized and sensorially evaluated. Structural analysis using computer simulation for each peptide revealed that the presence of a polar group and hydrophobic bitter amino acids, the composition of hydrophobic regions, the spatial orientation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…In addition, it appears that the peptide sequence, volume, and spatial structure also exert an effect on the perception of bitter taste (Kim, Yukio, Kim, & Lee, ). As the peptide length has been shown to increases, the bitterness is enhanced as the larger peptide chain length can increase the interactions with bitter receptors (Fu et al, ; Kim et al, ). Moreover, small hydrophobic peptides may lead to bitterness of protein hydrolysates (Matoba & Hata, ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it appears that the peptide sequence, volume, and spatial structure also exert an effect on the perception of bitter taste (Kim, Yukio, Kim, & Lee, ). As the peptide length has been shown to increases, the bitterness is enhanced as the larger peptide chain length can increase the interactions with bitter receptors (Fu et al, ; Kim et al, ). Moreover, small hydrophobic peptides may lead to bitterness of protein hydrolysates (Matoba & Hata, ).…”
Section: Resultsmentioning
confidence: 99%
“…Hydrophobicity, primary sequence, spatial structure, molecular weight, and bulkiness of peptides have been studied as possible influences in bitter taste of hydrolysates (Kim, Kawamura, Kim, & Lee, 2008). Several research groups found that Alcalase has the tendency to hydrolyze at hydrophobic amino acid residues, which cause a high bitterness (Adler-Nissen, 1986;Ishibashi et al, 1988).…”
Section: Effects On the Bitternessmentioning
confidence: 99%
“…The presence of proline residues has been found to be a major contributor to peptide bitterness (Ishibashi et al, 1988). It has recently been demonstrated that bitterness is determined by polarity, hydrophobicity, and the spatial structure of the peptides (Kim, Yukio, Kim, & Lee, 2008).…”
Section: Refined Oil Storage and Oil Flavor Chemistrymentioning
confidence: 99%